Long-term alterations in somatosensory functioning in survivors of childhood cancer. Issue 6 (25th June 2022) - Tutelman, Perri R.; Chambers, Christine T.; Cornelissen, Laura; Fernandez, Conrad V.; Flanders, Annette; MacLeod, Julia; Sherry, Simon B.; Stewart, Sherry H.; Urquhart, Robin; de Gagne, Sitara; Guilcher, Gregory M.T.; Hashmi, Javeria; et al.
Abstract : Supplemental Digital Content is Available in the Text. Pervasive somatosensory changes are present in survivors of childhood cancer years after the completion of treatment and are associated with demographic, clinical, and psychosocial factors. Abstract: Cancer and its treatment can have lasting consequences on somatosensation, including pain, which is often underrecognized and undertreated. Research characterizing the impact of cancer on pain and sensory processing in survivors of childhood cancer is scarce. This study aimed to quantify generalized differences in pain and sensory processing in survivors of childhood cancer compared with reference data using a standardized thermal and mechanical quantitative sensory testing (QST) protocol. The association between demographic, clinical (eg, leukemia vs other cancers and treatment exposures), and psychosocial (eg, anxiety and pain catastrophizing) variables and sensitivity to pain and sensory stimuli were also evaluated. Participants were 56 survivors of various types of childhood cancer (52% male, Mage = 13.5 years, SD = 3.2, range = 8-17 years). On average, children were 7 years (SD = 4.1, range = 1.2-16.5) post treatment. Almost all participants (86%) had at least 1 abnormal QST parameter compared with age- and sex-matched reference data; however, few participants self-reported the presence of sensory abnormalities. Generally, participants exhibited reduced sensitivity across the QST parameters examined ( P s < 0.05, ds = 0.40-3.45). A significant minority (45%) also exhibited pain sensitization ( P <0.001, d = 0.42). Several risk factors for changes in sensory processing were identified, including current age, history of leukemia, certain treatment exposures (eg, vincristine cumulative dose, major surgery, and bone marrow or stem cell transplant), time off treatment, and higher anxiety and pain catastrophizing scores. Overall, this study demonstrated that somatosensory changes are prevalent in survivors of childhood cancer years after the completion of treatment. Future research is needed to understand long-term implications of altered somatosensation in this complex population.